Enhancing Customer–Supplier Coordination Through Customer-Managed Inventory - Chen, Shi; Cohen, Morris A.; Lee, Hau (Management Science, 2024)
In recent years, there has been an increasing trend in supply chains to employ a “control tower” approach to improve supply chain performance. One such strategy is customer-managed inventory (CMI) in which the customer (the downstream party) controls the inventory of the supplier (the upstream party). However, the optimal design of the inventory control policy and the required incentive structure for CMI has not been fully explored in the related literature. In this paper, we develop a two-echelon model consisting of a supplier and a customer that captures the interaction between both decision makers. Analysis of this model indicates that achieving the potential benefits of CMI requires suitable incentive mechanisms to be put in place. The two-echelon inventory system model, however, does not give closed-form solutions, which are required to generate an optimal solution to the inventory control and incentive problem. To address this challenge, we propose an approximate model, which decouples the two-echelon model into two newsvendor-type models with each party operating a single-echelon system. This approximate model requires the introduction of additional cost parameters so that the decoupled model captures the cost implications of supplier shortages in the original two-echelon model. By developing appropriate values for these cost parameters, the approximate model yields near optimal results. Analysis of the solution reveals important operational factors that determine which environments are conducive for CMI and conditions for Pareto improvement of all stakeholders. This paper was accepted by Jayashankar Swaminathan, operations management. Supplemental Material: The online appendix and data files are available at https://doi.org/10.1287/mnsc.2021.03658 .